Antibiotic prophylaxis in oral and maxillofacial surgery: an integrative review (Research, Society and Development, 2023)
Infections that occur during the perioperative period of oral and maxillofacial surgeries are recurrent complications of daily dental practice. The selected antibiotic must be bactericidal and effective against the most common microorganisms that cause infection associated with the procedure to be performed. In this sense, this study aimed to review the literature about antibiotic prophylaxis in oral and maxillofacial surgery. For the construction of this article, a bibliographical survey was carried out in the databases SciVerse Scopus, Scientific Electronic Library Online (Scielo), U.S. National Library of Medicine (PUBMED) and ScienceDirect, with the help of the Mendeley reference manager. The articles were contemplated between the years 2000 to 2022. The main results show that the use of prophylactic antibiotics can reduce the risk of SSI in more complex and larger procedures, such as head and neck cancer surgery. On the other hand, when it comes to dentoalveolar surgery, the literature is still not clear about the effectiveness of prophylaxis with antimicrobials. For removal of third molars, antibiotic therapy is of uncertain benefit for healthy patients, but no evidence was found for patients with pre-existing systemic conditions. Overall, a multitude of different regimens were administered regardless of the respective surgical procedure.